Inovasi Produk Home Decor JIIB Sebagai Sarana Penghias Ruangan dan Relaksasi - Steffi Augusta Winata; Rendy Iswanto (Universitas Ciputra Surabaya, 2018)
This journal is written for a research focused on the business development of Jiib. Shortly, Jiib is an home decoration business, with concrete based, that is visually developed and uses the theories of entrepreneurship for its development. The objective of this research is to make a fixed model of the business, depends on the market demand, followed by design concept that can be applied in accordance with the market target, and as well as the strategies, visually and theoretically that is relevant with the market’s condition in this era. In this research, the methods used are primer data submission from some interviewees and direct market test to audience, and secondary data from theories that are picked from literature studies of existing books and journals. The final result of this research is a settled business model depends on the market demands, and the developed visuals that can be implemented to the brand relevantly for a long time.